PENGARUH BUDAYA ORGANISASI TERHADAP PERSONAL VALUE DAN PERILAKU IHSAN PEGAWAI UIN MAULANA MALIK IBRAHIM MALANG - Ekowati, Vivin Maharani; Mu’is, Achmad (IQTISHODUNA, 2017)
Abstract: For Muslims, benevolent’s behavior is highly recommended, because its a good behavior. To beable to compete to provide services for the patient, the nurse should be able to provide services based on thebenevolent’s behavior. The purpose of this study is to examine, test, and evaluate the influence of spiritualleadership, workplace spirituality, job satisfaction and benevolent’s behavior. The study conducted in RSIAisyiyah of Malang. Research population was all nurses. The Research samples were 60 nurses. Quistionareused to collect data from RSI Aisyiyah of Malang and the research data was analysis using PLS (Partial LeastSquare). The result showed that spiritual leadership significantly influenced workplace spirituality, spiritualleadership had no significantly influenced job satisfaction, spiritual leadership had no significantly influencedbenevolent’s behavior. Workplace spirituality significantly influenced job satisfaction, Workplace spiritualityhad no significantly influenced benevolent’s behavior, job satisfaction significantly influenced benevolent’sbehavior. Based on the result, it can be concluded that job satisfaction is valuable organizational component.This component may become on organization’s core competencies for improving benevolent’s behavior, whichare as sources of organizational competitive strengths in facing the rapidly changing business environments.